Factors Associated With Changes in Body Composition Shortly After Orthotopic Liver Transplantation: The Potential Influence of Immunosuppressive Agents. Issue 8 (August 2016) - Brito-Costa, Ana; Pereira-da-Silva, Luís; Papoila, Ana Luísa; Alves, Marta; Mateus, Élia; Nolasco, Fernando; Barroso, Eduardo
Abstract : Background: This study aimed to determine factors associated with body composition changes shortly after liver transplantation (LTx), including the influence of immunosuppressive agents. The combined resting energy expenditure (REE) and handgrip strength provided a valuable assessment in data interpretation of body composition. Methods: This observational single-center study included a cohort of consecutive end-stage liver disease patients with indications for LTx over 2 years. Cyclosporine was preferred for diabetic, hepatitis C–infected, and human immunodeficiency virus–infected patients per the transplant center protocol. Subjective Global Assessment, handgrip strength, multifrequency bioelectrical impedance analysis, and REE measurements were collected. The assessments were performed before LTx (T0) and at medians of 9 (T1) and 36 (T2) days after LTx. The fat mass index (FMI) and lean mass index (LMI) were surrogates of adiposity and skeletal muscle, respectively. Multiple linear regression analysis was used. Results: Fifty-six patients with a mean age of 53.7 (8.5) years were included; 87.5% were men. Preoperative Subjective Global Assessment undernourishment (β-estimate = 17.9; P = 0.004) and of drug addiction absence (β estimate = 14.6; P = 0.049) were associated with FMI increase. Higher REE at T1 (per 100 kcal) was associated with LMI increase (β estimate = 1.70; P = 0.012) and body cell mass increase (β estimate = 1.60; P = 0.049). The cyclosporine-based regimen was associated with FMI decrease (β estimate = −25.64; P < 0.001) and LMI increase (β estimate = 23.76; P < 0.001) when compared with a tacrolimus-based regimen. Steroids did not affect body composition. Conclusions: The cyclosporine-based regimen was independently associated with decreased adiposity and increased skeletal muscle compared with the tacrolimus-based regimen. Future randomized controlled trials are needed to confirm these findings. Abstract : Detailed physiological studies were performed in a liver transplant cohort. Decreased fat mass and increased lean mass was associated with cyclosporine but not tacrolimus therapy but immunosuppression assignment was not controlled. Supplemental digital content is available in the text.